A Contemporary Review of Plasminogen Activator Inhibitor Type 1: Structure, Function, Genetic Architecture, and Intracellular/Extracellular Roles - Wortley, Jacob; Vu, Justin; Soogoor, Neha; Becerra, Mebeli; Sathyamoorthy, Mohanakrishnan (TH Open, 2025)
Plasminogen activator inhibitor type 1 (PAI-1) is the key regulator of the fibrinolytic system, thereby acting as a potent mediator in thrombosis. Plasminogen activators such as PAI-1 mediate the conversion of the inactive zymogen plasminogen to plasmin, an active serine protease. As a member of the serpin superfamily, the highly conserved structure of PAI-1 is critical for its regulatory function. This review elucidates PAI-1 structure, function, and genetic architecture, and then discusses intracellular and extracellular functions that have broad implications for proliferative signaling and cell death, angiogenesis, cellular transit, and emerging roles in cancer biology. By understanding the complex and elaborate mechanism of PAI-1 in the fibrinolytic system and as a biomarker, PAI-1 may have broad implications across many disease states not related to its historical roles in fibrinolysis and thrombosis.
Keywords: PAI-1; extracellular matrix; genetics; fibrinolytic system; cell migration; cell proliferation